The morphology of Great Geomagnetic Storms recorded at Alibag for the period 1905 to 1945 : Part 11- The Disturbance local time inequality, DS and the disturbance daily variation, SD - YACOB, A.; SASTRI, N. S. (MAUSAM, 1966)
In continuation of results of storm-time disturbance variations Dst(H,E,Z) presented in Part I of the paper, the characteristics of disturbance daily variation, SD, and the disturbance local time inequality, DS, in the magnetic elements H, E and Z, as derived from 74 great sudden commencement storms recorded at Alibag during the period 1905 to 1945 are examined and discussed here. The DS (H) and SD (H) predominate over those in the elements E and Z. The magnitude of DS(H) during the main phase of the storm is large and decreases rapidly during the recovery phase. The phase angle of the first harmonic of DS(H) increases systematically with storm-time, especially during the first five 6-hour intervals of storm-time. The DS and SD variations for Alibag compare well with those for Honolulu and Zikawei given by Sugiura and Chapman, while the first harmonic of DS for Huancayo appears to be enhanced in a small measure. The SD variations are similar in magnitude and phase to those derived by Moos for Colaba (Bombay) for the period 1872 to 1904. The storm-time courses of D8t (H) and DS(H) for Alibag are about parallel to each other with a tendency for the minimum in DS(H) to be reached earlier than that of D8t (H)and their decay rates are about the same especially towards the later stages of their courses. Two decay rates are, however, noticed in the recovery phase of the average great storm. The decay rate of the earlier portion of the recovery phase is more rapid than that of the later portion, indicating the probability of two ring currents being associated with geomagnetic storms.